Upper limits of HO2 in the atmosphere of Mars from the ExoMars Trace Gas Orbiter - Alday, J; Trokhimovskiy, A; Belyaev, DA; Fedorova, AA; Holmes, JA; Patel, MR; Mason, JP; Lefèvre, F; Olsen, KS; Montmessin, F; Korablev, O; Baggio, L; et al. (Oxford University Press, 2024)
Odd-hydrogen (HOx⁠) species have a crucial role in regulating the chemistry of the atmosphere of Mars and are important to understand some of the most fundamental aspects regarding its atmospheric composition such as the long-term stability of CO2⁠⁠. Despite the key role of these species for our understanding of the Martian photochemistry, there is little observational evidence constraining their abundances. In this study, we use infrared solar occultation observations from the Atmospheric Chemistry Suite aboard the ExoMars Trace Gas Orbiter to search for spectral signatures of HO2⁠ in the atmosphere of Mars. In our analysis of the data, we retrieve vertical profiles of pressure, temperature, and water vapour mixing ratio, but are unable to confidently detect the presence of HO2⁠ features in the spectra. We report upper limits of 15 ppbv (5σ⁠), which represents an order of magnitude improvement with respect to previous investigations. Comparing the derived upper limits with the expectations from 3-dimensional Global Climate Models, we find that approximately an order of magnitude improvement in the instrument sensitivity would be required to detect this molecule and/or constrain the models.